2017
DOI: 10.1016/j.drugalcdep.2017.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of manual but not saccadic response inhibition following acute alcohol intoxication

Abstract: A B S T R A C TBackground: Alcohol impairs response inhibition; however, it remains contested whether such impairments affect a general inhibition system, or whether affected inhibition systems are embedded in, and specific to, each response modality. Further, alcohol-induced impairments have not been disambiguated between proactive and reactive inhibition mechanisms, and nor have the contributions of action-updating impairments to behavioural 'inhibition' deficits been investigated. Methods: Forty Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 78 publications
(115 reference statements)
0
27
0
Order By: Relevance
“…Even changes to response modality-saccadic versus manualwhich might not intuitively be associated with different stimulusdriven effects, in fact do affect the balance of drive from different sensory pathways (Bompas & Sumner, 2008), and thus the delay and amplitude of stimulus-driven activity (see Bompas et al, 2017 for discussion and demonstration of the presence of dips in the manual modality). This could be part of the reason why SSRT differs between modalities (Boucher, Stuphorn, et al, 2007) and possibly also why saccadic and manual SSRT are differentially susceptible to influences such as alcohol (Campbell et al, 2017). Some task designs (e.g., manual responses with low-salience stop signals) may entail a sufficiently small automatic effect that explicitly including it in models would not alter conclusions in any important way.…”
Section: The Importance Of Sensory Pathway Dynamics In Motor Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even changes to response modality-saccadic versus manualwhich might not intuitively be associated with different stimulusdriven effects, in fact do affect the balance of drive from different sensory pathways (Bompas & Sumner, 2008), and thus the delay and amplitude of stimulus-driven activity (see Bompas et al, 2017 for discussion and demonstration of the presence of dips in the manual modality). This could be part of the reason why SSRT differs between modalities (Boucher, Stuphorn, et al, 2007) and possibly also why saccadic and manual SSRT are differentially susceptible to influences such as alcohol (Campbell et al, 2017). Some task designs (e.g., manual responses with low-salience stop signals) may entail a sufficiently small automatic effect that explicitly including it in models would not alter conclusions in any important way.…”
Section: The Importance Of Sensory Pathway Dynamics In Motor Decisionmentioning
confidence: 99%
“…BOMPAS, CAMPBELL, AND SUMNER However, in our present results, the latency remains relatively short for the top-down signals. SSRT is normally estimated as between 100 and 150 ms in humans for saccades (Campbell, Chambers, Allen, Hedge, & Sumner, 2017;Hanes & Carpenter, 1999). In our model there are two relevant input delays: visual and endogenous delay.…”
mentioning
confidence: 99%
“…However, in our present results, the latency remains relatively short for the top-down signals. SSRT is normally estimated as between 100 and 150 ms in humans for saccades (Campbell, Chambers, Allen, Hedge, & Sumner, 2017;Hanes & Carpenter, 1999). In our model there are two relevant input delays: visual and endogenous delay.…”
Section: How Fast Are Top-down Commands?mentioning
confidence: 99%
“…Even changes to response modality -saccadic vs manual -which might not intuitively be associated with different stimulus-driven effects, in fact do affect the balance of drive from different sensory pathways (Bompas & Sumner, 2008), and thus the delay and amplitude of stimulus-driven activity (see Bompas et al, 2017for discussion and demonstration of the presence of dips in the manual modality). This could be part of the reason why SSRT differs between modalities (Boucher, Stuphorn, et al, 2007) and possibly also why saccadic and manual SSRT are differentially susceptible to influences such as alcohol (Campbell et al, 2017). Some task designs (e.g.…”
Section: The Importance Of Sensory Pathway Dynamics In Motor Decisionmentioning
confidence: 99%
“…These results implied that heavy drinkers were relying on reactive control, whereas light drinkers were employing proactive control to filter out the context of the prior image. Conversely, Campbell et al (2017) demonstrated that alcohol intoxication increased motor SSRTs but did not influence proactive slowing. Indeed, this emphasises the simplistic conceptualization of inhibitory control in the majority of prior research and the need to break inhibitory control down into its component processes to further understanding.…”
Section: Introductionmentioning
confidence: 96%